1985
DOI: 10.1007/bf03348517
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine decreases release of luteinizing hormone releasing hormone from superfused rat mediobasal hypothalamus

Abstract: The effects of dopamine hydrochloride (DA) on the releases of LHRH and LH were examined in a serial sequential double chamber perifusion system by perifusing the mediobasal hypothalamus including the preoptic area and/or pituitaries excised from diestrus female rats. DA, perifused at a dose of 4.2 X 10(-4) M, significantly (p less than 0.05) lowered LH secretion from the pituitary in series with the hypothalamus 40-80% below the preinfusion level, but it had no effect on LH efflux from the pituitary perifused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These results are consistent with the hypothesis that dopaminergic system is one of the main inhibitory neuronal systems that control the development of the reproductive systems (Becu-Villalobos and Libertun, 1995) and productivity (Sotowska-Brochocka et al, 1994). In rodents, the biological functions of DA on productivity had been confirmed by administrating exogenous DA that significantly reduced the LHRH level from the hypothalamus and lowered LH secretion from the pituitary (Tasaka et al, 1985). Provided studies had shown that endogenous DA secreted in the hypothalamus exhibited catecholamine's tonic inhibition of Luteinising hormone-releasing hormone (LHRH) release (Contijoch et al, 1992) and suppression LH secretion (Martin et al, 1981).…”
Section: Dopamine and Selection For High Productivity And Longevity Wsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with the hypothesis that dopaminergic system is one of the main inhibitory neuronal systems that control the development of the reproductive systems (Becu-Villalobos and Libertun, 1995) and productivity (Sotowska-Brochocka et al, 1994). In rodents, the biological functions of DA on productivity had been confirmed by administrating exogenous DA that significantly reduced the LHRH level from the hypothalamus and lowered LH secretion from the pituitary (Tasaka et al, 1985). Provided studies had shown that endogenous DA secreted in the hypothalamus exhibited catecholamine's tonic inhibition of Luteinising hormone-releasing hormone (LHRH) release (Contijoch et al, 1992) and suppression LH secretion (Martin et al, 1981).…”
Section: Dopamine and Selection For High Productivity And Longevity Wsupporting
confidence: 88%
“…In rodents, the biological functions of DA on productivity had been confirmed by administrating exogenous DA that significantly reduced the LHRH level from the hypothalamus and lowered LH secretion from the pituitary (Tasaka et al, 1985). The later had been verified by either administrating of DA receptor agonist 2-Br-alpha-ergocryptine to lower plasma LH levels (Owens et al, 1980) or blocking DA inhibitory effect by use of DA receptor blocker halperidol (Tasaka et al, 1985). In hens, increase in dopaminergic activity inhibited the release of LH by exerting an inhibitory influence on the LHRH containing cells in the hypothalamus (Macnamee and Sharp 1989).…”
Section: Dopamine and Selection For High Productivity And Longevity Wmentioning
confidence: 99%
“…However, the mechanisms underlying dopaminergic regulation of gonadotropic hormone release remain unclear, particularly in fish. Previous studies demonstrate that in tetrapods, dopamine inhibits GnRH1 release (Ching and Lin, 1994;Lacau-Mengido et al, 1993;Owens et al, 1980;Tasaka et al, 1985) via actions at both the hypothalamic soma of GnRH1 neurons and their synaptic terminals within the portal vasculature (Contijoch et al, 1992;Corio et al, 1990;Kuljis and Advis, 1989;Lehman et al, 1988;Pehrson et al, 1983;Ugrumov et al, 1989). In fish, dopamine was thought to act primarily within the pituitary, reducing gonadotropin release either indirectly, by suppressing GnRH1-releasing axons, or directly, by inhibiting pituitary gonadotropes (Levavi-Sivan et al, 1995;Vacher et al, 2002;Van Goor et al, 1998;Yu and Peter, 1992;Yu et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Despite conclusive evidences of the importance of catecholaminergic influences in the control of hypothalamic LHRH secretion (1 S), the role of dopamine in the functional control of the LHRH secreting neuron remains controversial. Evidence exists to support a stimulatory and/or and inhibitory role of dopamine in the maintenance of LHRH secretion (1 3, 14, [16][17][18][19][20][21]37). In adult rats the mechanism of dopamine induced stimulation of LHRH efflux from the medium basal hypothalamus perifused in vitro is probably attributable to the action of dopamine in causing release of endogenous noradrenaline (14); and dopamine inhibition of LHRH release from medium basal hypothalami is apparently achieved by increasing endogenous opioid activity (18).…”
Section: Discussionmentioning
confidence: 99%